Concentrations of essential and non-essential elements in eastern North Pacific killer whales (Orcinus orca) - Catherine F. Lo; Joseph K. Gaydos; Robert Poppenga; Lynne Barre; Kathy Burek-Huntington; John Calambokidis; Paul Cottrell; Debbie Duffield; Jessica L. Huggins; Dyanna M. Lambourn; Jim Rice; Heindrich N. Snyman; et al. (PLoS ONE, 2026)
Essential and non-essential elements can harm marine wildlife and impact ecosystems. Using liver (n = 35) and kidney (n = 17) samples from 35 animals from three distinct killer whale ( Orcinus orca ) ecotypes (fish-eating residents, mammal-eating transients, and offshore shark-eating specialists) stranded from California to Alaska and Hawaii, we determined elemental concentrations (arsenic (As), barium (Ba), beryllium (Be), calcium (Ca), cadmium (Cd), cobalt (Co), copper (Cu), chromium (Cr), iron (Fe), mercury (Hg), methylmercury (MeHg), manganese (Mn), molybdenum (Mo), magnesium (Mg), nickel (Ni), lead (Pb), selenium (Se), thallium (Tl), vanadium (V), and zinc (Zn)). Also, we evaluated associations with demographic and genetic factors. Calves had lower Cd than other life stages in kidney and liver tissue. Adult females had higher liver Se than calves and higher total mercury (tHg) in kidney and liver than calves. Adult males had higher liver Cd, tHg, and Se than calves. Residents had higher liver Mg, Mn, and Mo than transients. Linear regression showed life stage had some effect on the concentration of kidney Hg, and on the concentration of liver Mg, Mn, Mo, Cd, Hg, and Se. A prior study found no microscopic evidence of toxicosis in the tissues of examined animals. Population had some effect on liver Cd and Mg. Mean ± SD Se:Hg molar ratios in kidney (0.871 ± 0.645) and liver (0.932 ± 0.940) were consistent with prior research (at or nearly 1:1), but ratios based on factors varied in kidney. These results expand knowledge of elements in northeastern Pacific killer whales.